Musyarakah Financing Contribution to The Profitability Of Bank Syariah Indonesia (BSI) - Komala, Adeh Ratna; Maryati, Mari; Hinggis, Fatya Febrianti; Fitri, Diana (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2023)
Financing products offered by Islamic banks are diverse, but the most popular one is the murabahah contract. However, the desired contract from Islamic banks is the musyarakah financing because it is the mainstay of the Islamic banking industry. The purpose of this research is to examine the contribution of musyarakah financing to the profitability of Bank Syariah Indonesia (BSI). This study used a descriptive and verification method where the processed data were secondary financial reports with musyarakah financing and profitability variables, and Return on Assets (RoA) was used as the indicator. Financial data was taken from financial reports for three years, namely 2019, 2020, and 2021. The data were then processed using SPSS version 23.0 with a simple linear regression analysis method. The results of the study show that the musyarakah financing variable has an effect on the profitability of BSI. In conclusion, musyarakah financing is an ideal product for Islamic banks because it provides the same opportunity for partners to contribute in the form of capital or expertise.